ダイ34ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1992-1993 - 成瀬, 廉二; ナルセ, レンジ; Naruse, Renji (1994)
P(論文) 第34次南極地域観測隊は, 越冬隊(佐藤夏雄隊長)39名, 夏隊(成瀬廉二副隊長)16名で編成され, さらに交換科学者として, 中国から1名が越冬隊に, オーストラリアから1名が夏隊に参加した。砕氷艦「しらせ」は, 1992年11月14日東京港を出港し, 12月17日からリュツォ・ホルム湾の厚さ2∿3m強の定着氷に入り, 砕氷航行の後, 30日昭和基地に接岸した。12月18日から昭和基地へのヘリコプターによる輸送が始まり, 接岸後の氷上輸送, 貨油輸送を含め, 1993年1月中旬までに計960tの物資の輸送が完了した。昭和基地における夏期の建設作業は, 12月19日より2月9日までの間に管理棟内部設備等, 当初計画の工事をほぼ完了した。この間, 南極周回気球3機の打ち上げに成功するとともに, 重力絶対測定では600個以上の有効データが得られた。また, 大陸沿岸の露岩地域では正味43日間にわたり地質, 地形, 測地, 生物等の野外調査を, 氷床内陸では1カ月間の中継拠点往復デポ旅行を実施した。2月10日, 昭和基地最終便により第34次夏隊全員が「しらせ」へ帰着した。「しらせ」は2月13日流氷縁を離脱し, リュツォ・ホルム湾沖では4日間にわたり海底地形測量を実施し, その後19日から23日までアムンゼン・ケーシー湾にて露岩域の地学調査, 海洋生物観測, 3月2日から4日までプリッツ湾にて海洋生物観測を行った。生物観測では, トロール等により多種類の底生生物, 中層性魚類, プランクトン等が採集された。その後, 船上観測を行いつつ帰路につき, 3月21日にオーストラリア・シドニーに入港した。なお, 海洋停船観測は, 往路4測点, 復路11測点にて実施した。第34次夏隊は第33次越冬隊とともに, 28日シドニー発空路, 同日成田に帰着した。 Summer activities of the 34th Japanese Antarctic Research Expedition (JARE-34) in 1992-1993 are described. The expedition consisted of 39 members of the wintering party, 16 members of the summer party, and two scientists from China and Australia (one for the wintering and one for the summer party). The icebreaker SHIRASE left Tokyo on 14 November 1992 and arrived at Syowa Station on 30 December. Transportation of cargoes to Syowa Station and to Station S16 (600m a. s. l.) on the ice sheet was started from 18 December; a total of 960t were freighted by helicopters and oversnow vehicles until the middle of January 1993. Construction of a three-story house was completed at the central part of Syowa Station before early February 1993. From 19 December 1992 to 9 February 1993,various studies were carried out at Syowa Station. Observations of the upper atmosphere using Polar Patrol Balloons were successfully accomplished three times. A number of gravity data with high accuracy were obtained by absolute measurements of gravity. In the coastal regions of Lutzow-Holm Bay and the Prince Olav Coast, geological, geomorphological, geodetic and biological surveys were carried out during 43 days. An oversnow traverse to/from the Inland Camp (74°S, ...